ESC, ESCL and their roles in Polycomb Group mechanisms. - Ohno, K.; McCabe, D.; Czermin, B.; Imhof, A.; Pirrotta, V. (Mechanisms of Development, 2008)
The Drosophila esc gene is a Polycomb Group (PcG) gene whose product is essential for histone H3 K27 methylation and PcG silencing yet genetic analysis indicated that its product was needed only in the very early embryo. We know now that escl, a close homologue of esc exists in the Drosophila genome. In contrast with earlier studies, we find that both esc and escl are expressed at all stages of development. We show that three major differences between the two genes are in the transcriptional control, which allows esc to make a much stronger maternal contribution; in the splicing efficiency, which makes a major difference in the early escl function; and in the lower participation of ESCL in the PRC2 complex and lower enzymatic activity of the resulting complex. Both genes can sustain normal development in the absence of the other except for the critical role provided by maternal esc product in early embryonic development. Finally, using zygotic mutations in both genes, we show that the gradual loss of function of PRC2 activity leads first to a loss of histone H3 K27 methylation and only at a later stage to a gradual loss of PRC1 binding to chromatin.